GUANFACINE MECHANISMS, CLINICAL EFFICACY, AND ROLE IN MODERN ADHD PHARMACOTHERAPY – A REVIEW - Bojarska, Wiktoria; Białek, Agnieszka Barbara; Januszczak, Radosław; Gilarska, Gabriela Anna; Cholewa, Julianna; Bojarska, Sylwia; Sygacz, Maja (International Journal of Innovative Technologies in Social Science, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder worldwide. It affects cognitive, behavioural, and social functioning across the lifespan. Symptoms such as inattention, hyperactivity, and impulsivity can significantly impair academic, occupational, and interpersonal outcomes. Stimulant medications, including methylphenidate and amphetamine derivatives, remain the first-line treatment due to their robust efficacy. However, their use is often limited by side effects, risk of misuse, and incomplete response in a substantial subset of patients. These limitations have driven growing interest in non-stimulant pharmacotherapies that target alternative neurobiological mechanisms. Guanfacine, a selective alpha-2A adrenergic receptor agonist, has emerged as a promising non-stimulant option. By enhancing prefrontal cortex signalling through alpha-2A receptor agonism, guanfacine stabilises neuronal firing, which improves working memory, attention regulation, and inhibitory control. Clinical studies indicate that guanfacine is particularly effective in reducing hyperactivity and impulsivity and can serve as an adjunctive therapy in patients with partial stimulant response. Its sedative effects may also provide additional benefits for comorbid sleep disturbances and anxiety, while its non-stimulant profile lowers the risk of abuse. Common adverse effects include sedation, hypotension, and bradycardia, necessitating careful dose titration and monitoring. Evidence regarding long-term efficacy and safety, particularly in adults, remains limited, emphasising the need for further research to optimise individualised treatment strategies. Nonetheless, guanfacine represents an important addition to ADHD pharmacotherapy, offering clinicians a valuable tool to tailor interventions according to patient-specific symptom profiles and treatment goals.